Формування фінансового потенціалу підприємства - Демченко, Іван Володимирович; Демченко, Иван Владимирович; Demchenko, Ivan (My University, 2018)
UK: Проаналізовано теоретичні підходи до трактування категорії «фінансовий потенціал підприємства». Визначені основні складові фінансового потенціалу підприємства. Розкрито сутність окремих складових на прикладі сільськогосподарського підприємства. Показано взаємозв’язок фінансової безпеки та фінансового потенціалу підприємства. EN: Ensuring effective activity and further development are capable of exclusively those entities that are able to build a number of levers and counteract numerous risks of state gifts: the dependence of the corporate sector on imports, the low level of domestic consumer demand of the country, the instability of the national course money units-these and so on. Under such conditions, financial security of the subject, which correlates with the very ability to exist and the system of counteraction to the risks of state-building, serves as the basis for the formation, and in the future - realization of the financial potential of the enterprise.
Formation of financial potential of enterprise
Keywords: фінансовий потенціал підприємства; підприємство; фінансові результати; фінансовий стан; фінансові показники; фінансова безпека; financial potential of the enterprise; enterprise; financial results; financial status; financial indicators; financial security